CODE-EHR best practice framework for the use of structured electronic healthcare records in clinical research. (29th August 2022) - Kotecha, Dipak; Asselbergs, Folkert W; Achenbach, Stephan; Anker, Stefan D; Atar, Dan; Baigent, Colin; Banerjee, Amitava; Beger, Birgit; Brobert, Gunnar; Casadei, Barbara; Ceccarelli, Cinzia; Cowie, Martin R; et al.
Abstract : Big data is central to new developments in global clinical science aiming to improve the lives of patients. Technological advances have led to the routine use of structured electronic healthcare records with the potential to address key gaps in clinical evidence. The covid-19 pandemic has demonstrated the potential of big data and related analytics, but also important pitfalls. Verification, validation, and data privacy, as well as the social mandate to undertake research are key challenges. The European Society of Cardiology and the BigData@Heart consortium have brought together a range of international stakeholders, including patient representatives, clinicians, scientists, regulators, journal editors and industry. We propose the CODE-EHR Minimum Standards Framework as a means to improve the design of studies, enhance transparency and develop a roadmap towards more robust and effective utilisation of healthcare data for research purposes.